The Sephardim in the Holocaust : a forgotten people - Lévy, Isaac Jack 1928-2020 (Jews and Judaism: history and culture, 2020)
"The Sephardim in the Holocaust: A Forgotten People embraces the Sephardim of all the countries shattered by the Holocaust and pays tribute to the memory of the more than 160,000 Sephardim who perished. Isaac Jack Lévy and Rosemary Lévy Zumwalt draw on a wealth of archival sources, family history (Isaac and his family were expelled from Rhodes in 1938), and more than one hundred fifty interviews conducted with survivors during research trips to Belgium, Canada, France, Greece, Israel, Mexico, the Netherlands, the former Yugoslavia, and the United States. Lévy follows the Sephardim from Athens, Corfu, Cos, Macedonia, Rhodes, Salonika, and the former Yugoslavia to Auschwitz. The authors chronicle the interminable cruelty of the camps, from the initial selections to the grisly work of the Sonderkommandos inside the crematoria, detailing the distinctive challenges the Sephardim faced, with their differences in language, physical appearance, and pronunciation of Hebrew, all of which set them apart from the Ashkenazim. They document courageous Sephardic revolts, especially those by Greek Jews, which involved intricate planning, sequestering of gunpowder, and complex coordination and communication between Ashkenazi and Sephardic inmates-all done in the strictest of secrecy. And they follow a number of Sephardic survivors who took refuge in Albania with the benevolent assistance of Muslims and Christians who opened their doors to give sanctuary, and traces the fate of the approximately 430,000 Jews from Morocco, Algiers, Tunisia, and Libya from 1939 through the end of the war. The author's intention is to include the Sephardim in the shared tragedy with the Ashkenazim and others. The result is a much needed, accessible, and viscerally moving account of the Sephardim's unique experience of the Holocaust"--